COMPARISON OF BUSINESS DISPUTE RESOLUTION THRU ARBITRATION BETWEEN INDONESIA AND THAILAND - Wahyuni, Luthfi Amanda; Riza, Faisal (Pena Cendekia Insani, 2026)
The resolution of business disputes through arbitration constitutes a form of private legal dispute settlement, particularly within the context of cross-border business relationships. In Indonesia and Thailand, the implementation of business dispute resolution through arbitration is conducted through several procedural stages, after which arbitral awards are final and binding. However, Thailand imposes a three-year time limit for the enforcement of arbitral awards, whereas Indonesia does not specifically regulate such a limitation. Differences in arbitration rules and practices between Indonesia and Thailand give rise to juridical consequences affecting the legal standing of arbitral awards and the effectiveness of their enforcement. This study aims to examine and compare the mechanisms of business dispute resolution through arbitration and the legal position of arbitral awards in Indonesia and Thailand. The research employs a normative juridical method using statutory and comparative approaches, supported by primary, secondary, and tertiary legal materials. Data collection was conducted through library research, and the data were analyzed qualitatively. The findings indicate that Law Number 30 of 1999 governs arbitration in Indonesia with more formal procedural characteristics and strong court involvement, particularly at the stage of award enforcement. In contrast, the Arbitration Act B.E. 2545 (2002), as amended by the Arbitration Act B.E. 2562 (2019), establishes a more flexible and contemporary arbitration system that adopts the principles of the UNCITRAL Model Law. The main obstacles to enforcement in Indonesia include excessive judicial intervention and lengthy bureaucratic procedures, whereas Thailand faces challenges in harmonizing domestic and international arbitration frameworks.